2013
DOI: 10.2337/db12-1374
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NF-κB Activity Impairs Vascular Function Through PARP-1–, SP-1–, and COX-2–Dependent Mechanisms in Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is associated with vascular dysfunction. We hypothesized that increased nuclear factor-κB (NF-κB) signaling contributes to vascular dysfunction in T2D. We treated type 2 diabetic (db−/db−) and control (db−/db+) mice with two NF-κB inhibitors (6 mg/kg dehydroxymethylepoxyquinomicin twice a week and 500 μg/kg/day IKK-NBD peptide) for 4 weeks. Pressure-induced myogenic tone was significantly potentiated, while endothelium-dependent relaxation (EDR) was impaired in small coronary arterioles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 46 publications
4
68
0
Order By: Relevance
“…We have provided in vivo evidence that NBD peptide dose-dependently attenuates NF-κB activation in the aorta and limits atheroma plaque formation in type 1 diabetic Apoe −/− mice. This finding is in agreement with that of a recently published report showing that NBD improved vascular dysfunction (in terms of myogenic tone and endothelium-dependent relaxation) in coronary and mesenteric resistance arteries from a mouse model of type 2 diabetes [45]. Importantly, we observed that NF-κB inhibition altered plaque composition and inflammation in mouse atherosclerotic lesions without affecting serum lipid levels.…”
Section: Resultssupporting
confidence: 82%
“…We have provided in vivo evidence that NBD peptide dose-dependently attenuates NF-κB activation in the aorta and limits atheroma plaque formation in type 1 diabetic Apoe −/− mice. This finding is in agreement with that of a recently published report showing that NBD improved vascular dysfunction (in terms of myogenic tone and endothelium-dependent relaxation) in coronary and mesenteric resistance arteries from a mouse model of type 2 diabetes [45]. Importantly, we observed that NF-κB inhibition altered plaque composition and inflammation in mouse atherosclerotic lesions without affecting serum lipid levels.…”
Section: Resultssupporting
confidence: 82%
“…The myogenic response is characterized by vasoconstriction in response to an increase of intraluminal pressure and vasodilatation in response to a decrease in intraluminal pressure and is an intrinsic vascular response that plays an important role in the local regulation of blood flow (Bayliss, 1902). Previous studies have shown that impaired small artery function is attributable to the enhanced myogenic response in diabetic animals (Lagaud et al 2001;Choi et al 2012;Kassan et al 2013). Interestingly, in the present study, we observed an enhanced myogenic response in the coronary arteries of type 2 diabetic mice associated with increased ER stress markers.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, patients with diabetes have a much higher risk of myocardial infarction (Diabetes Control and Complications Trial Research Group, 1993; UK Prospective Diabetes Study Group, 1998). It has been suggested that various factors, including metabolic factors, advanced glycation end-products and endothelial dysfunction, contribute to diabetes-induced vascular complications (Nogueira-Machado & Chaves, 2008;Kassan et al 2013;Manigrasso et al 2014). Although the link between diabetes and cardiovascular disease is not fully understood, it is considered that potentiation of the pressure-induced myogenic response and impaired endothelium-dependent relaxation are main characteristics of diabetic vascular dysfunction (Cai et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The IKK complex and NF-kB have been implicated in a variety of vascular diseases and complications, including obesity (Kassan et al, 2013), renal disease, and hypertension (Cardinale et al, 2012). In animal models, hypertensioninduced renal damage can be attenuated by endothelialspecific cell suppression of NF-kB (Henke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%